(untitled) (Journal of Parents and Teachers, 2013)
This article completes a series written by the same author about competences. This particular one talks about assessment. In the article, the author reviews the conceptions of assessment, analyses when and how a teacher should evaluate a student and shows the characteristics that should have the questions with which teachers make an assessment.